Egypt, Canaan, and Israel in ancient times - Redford, Donald B. (Princeton, N.J. : Princeton University Press, 1992)
An overview of the history and relations of Egypt and Western Asia from the Paleolithic period to the destruction of Jerusalem in 586 B.C.
Egypt and the Levant from prehistoric times to the Hyksos. Village, camps, and the rise of a colossus ; Upper and lower Egypt and the walled towns of Asia ; "Lo, the vile Asiatic!" ; "Trampling the foreign lands" : Egypt and Asia during the middle kingdom ; The Hyksos in Egypt -- The Egyptian empire in Asia. "Extending the frontiers of Egypt" ; The empire of the new kingdom ; Asia in Egypt : mosaic, not melting pot -- The great migrations. The coming of the sea peoples ; "These are the bene-yisrael--" -- Egypt and the Hebrew kingdoms. Horses and Pharaoh's daughter : Egypt and the united monarchy ; Egypt and Israel in the world of Assyria ; Specter or reality? : the question of Egyptian influence on Israel of the monarchy ; Four great origin traditions ; Egypt and the fall of Judah.
Includes bibliographical references and index.
Keywords: Egypt -- Relations -- Palestine; Palestine -- Relations -- Egypt; Egypt -- History -- To 332 B.C.; Palestine -- History -- To 70 A.D.